2010
DOI: 10.1016/j.jaci.2010.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Breast-feeding, aeroallergen sensitization, and environmental exposures during infancy are determinants of childhood allergic rhinitis

Abstract: Background Infant predictors of early childhood allergic rhinitis (AR) are poorly understood. Objective Identify environmental exposures and host factors during infancy that predicts AR at age three. Methods High risk children from Greater Cincinnati were followed annually from ages one to three. Allergic rhinitis (AR) was defined as sneezing, runny or blocked nose in the prior 12 months and positive skin prick test (SPT) to one or more aeroallergens. Environmental and standardized medical questionnaires d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 30 publications
2
64
0
1
Order By: Relevance
“…35 However, several studies have shown a positive effect of having been breast-fed exclusively for some time in children, and breast-feeding has been recommended for the prevention of atopic diseases. 12,14 Neither atopic dermatitis nor asthma showed significant associations with the course of AR over puberty. It might have been expected that at least atopic dermatitis would be a risk factor for the development of AR because, according to the atopic march theory, it usually precedes rhinitis and asthma.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…35 However, several studies have shown a positive effect of having been breast-fed exclusively for some time in children, and breast-feeding has been recommended for the prevention of atopic diseases. 12,14 Neither atopic dermatitis nor asthma showed significant associations with the course of AR over puberty. It might have been expected that at least atopic dermatitis would be a risk factor for the development of AR because, according to the atopic march theory, it usually precedes rhinitis and asthma.…”
Section: Discussionmentioning
confidence: 90%
“…9 Not only do hereditary factors and sex seem to play an important role in the development of AR 10,11 but also many environmental and lifestyle factors have been associated with increased risk of AR as well. 11 While breast-feeding, having siblings, and higher socioeconomic status have been shown to be inversely associated with the incidence of AR, [12][13][14] exposure to environmental tobacco smoke during pregnancy, as well as in infancy, might increase the risk of AR. 15 Thus far, there is a lack of predictive models for the course of AR, especially during the period of transition from childhood to adulthood.…”
mentioning
confidence: 99%
“…And similarly the prevalence in urban areas is higher than that of rural areas [2][3][4][5][6]. Perhaps more importantly, these studies show that the international patterns of disease prevalence cannot be explained by the current understanding of the etiology of these conditions [7].…”
Section: Allergic Rhinitis Prevalence Ratesmentioning
confidence: 97%
“…19 Recently, house dust LPS was reported to be either negatively or positively associated with the prevalence of allergic rhinitis, depending on the exposure level. 20 The immunomodulatory effects of flagellin are primarily mediated through stimulation of TLR5 on dendritic cells (DCs). 21 In the present study we show that a therapeutic dose of FlaB functioned as a tolerogenic adjuvant to generate regulatory dendritic cells (rDCs) and Treg cells and ameliorated asthma in 2 experimental models.…”
mentioning
confidence: 99%